Exploring The Relationship Between Body Mass Index (BMI), Body Weight Perception, And Weight Change Behaviour Among University Students in Urban Gujarat, India: A Cross-Sectional Study - Rajanikant Solanki; Hasmukh Shah; Tejas Prajapati (Medsci Publications, 2023)
Background: In the context of the rising trend of overweight and obesity, young people are more concerned about their weight. This study investigates the association between measured Body Mass Index (BMI), self-perception of body weight and weight change behavior among university students. Methods: This cross-sectional study assessed a sample of 415 university students aged 18-23 years residing in urban areas of Anand. Measures included weight, height, BMI, body weight perception and weight change behavior. The data were analyzed through descriptive statistics, the student's t-test and Chi-square test. Results: About 36.1% of the participants misclassified their weight category. More women than men felt overweight in relation to their actual body shape. Among normal-weight or underweight BMI participants, 44.4% of females and 31.8% of males were inappropriately trying to lose weight. Conclusions: The study showed a higher prevalence of weight perception and inappropriate weight change behaviour. It also observed that the correct perception of body weight influences the willingness to lose or gain weight. It is important to consider these issues while designing a public health campaign targeting obesity and healthy lifestyles.